Getting a PhD an action plan to help manage your research, your supervisor and your project - Finn, John A. 1972- (Routledge study guides, 2005)
This practical book provides a workable action plan to help students get a PhD. Illustrated throughout with examples from a wide range of academic disciplines the book includes exercises and points for reflection as well as info on research